The Asperger social guide : how to relate to anyone in any social situation as an adult with Asperger's syndrome - Edmonds, Genevieve (Paul Chapman, 2006)
The Asperger Social Guide is a pocket sized travel guide for adults with Asperger s syndrome exploring the social world. Genevieve and Dean have written a practical handbook based on their personal experiences. They know what people with Asperger s syndrome need to know and write in a clear and engaging style. I endorse their explanations, tips and strategies and will be recommending The Asperger Social Guide to my adult clients and those who support them . Professor Tony Attwood. T̀his looks like a book that our social skills groups and some of our schools could use Social skills are a big pr.